Spatiotemporal Distribution Characteristics and Influencing Factors of Dissolved Potentially Toxic Elements along Guangdong Coastal Water, South China - Gelin Kang; Hanbao Chen; Chuanqi Hu; Fangzheng Wang; Zuoda Qi (Journal of Marine Science and Engineering, 2024)
In this study, five potentially toxic elements (PTEs) (Hg, Pb, As, Zn, and Cu) and five physicochemical factors (pH, dissolved oxygen, salinity, chlorophyll a, and chemical oxygen demand) relating to surface seawater were measured along the coast of Guangdong Province (GD), China, during three seasons in 2019. Comprehensive analyses were conducted to explore the distribution characteristics, pollution degrees, and influencing factors of PTE. The results showed that the concentrations of PTE varied spatially and seasonally due to these elements’ complex sources and behaviors. Pb was the most abundant toxic element, reaching considerable contamination levels. Overall, the average pollution degrees of Cu, As, and Zn were higher around the east coast of GD, while Hg and Pb levels were higher in the west coast region of GD. The correlation analysis showed that the variation of different physicochemical parameters had different degrees of influence on PTE transport and transformation. This study can help environmental managers gain deeper insight into the influence of complex factors on PTE and improve the efficiency of pollution control in this significant subtropical coastal area.